A STUDY ON THE TIDAL WAVE-INFLUENCED DRAINAGE SYSTEM IN THE CITY OF AMBON - Dominggus Nara NIM :25004019, Obednego
Abstract: Geographically, Ambon is located in 38-48 LS and 1288-1298 BT, possesses various typography and is also passed through by several small rivers, one of which is the Waitomu river-area of the analysis object. It is much comprehensible that this area undergoes the up and down of tidal wave. The study covers hydrology analysis and tidal wave analysis with existing condition which are used as the input for modeling. Forming the model based on the physical conditions and hydraulic characteristics is the way this research was conducted. The modeling was done by using the Duflow 2.04 program, which is able to compute the non-soft flow and one-dimension review. By entering the requirements limit as the input of the simulation, there can be found the accumulation of row and the elevation fluctuation of water level that are influenced by time. As the result of this modeling, a solution can be recommended by considering hydraulic physical conditions. It is possible to raise a dam in every channel that its water level is passed from the maximum one at the existing channel.